Geographic Information System for Monitoring Agricultural and Rural Development: A Human Rights-Based Approach to Post-War Reconstruction in Ukraine - Shamil IBATULLIN; Oksana SAKAL; Roman DERKULSKYI; Andriy DOROSH; Vitaliy KRUPIN (Communications of International Proceedings, 2025)
This paper presents a conceptual framework for developing a geographic information system (GIS) designed to monitor agricultural and rural development in Ukraine with integrated human rights assessment components. The proposed system addresses critical challenges facing Ukraine's rural territories in the context of post-war reconstruction, including food security degradation, land resource management, infrastructure destruction, and protection of vulnerable population groups. The study outlines a comprehensive monitoring framework structured around six indicator blocks: security situation, food security, land resources and land use, agro-food system infrastructure, socio-economic conditions of rural territories, and human rights observance. The system architecture incorporates modular design principles, spatial database technologies, and advanced analytical capabilities to support evidence-based policy development and decision-making at multiple governance levels. Integration of geospatial analysis and socio-economic assessment methods aims to provide a tool for a human rights-based approach implementation into rural development management during Ukraine's post-war reconstruction.
Keywords: geographic information system; agricultural development monitoring; human rights-based approach; food security; land relations; rural development; post-war reconstruction; spatial analysis; Ukraine